METODE PENERAPAN PENDIDIKAN CHARACTER PADA ANAK SMK DALAM MELAKUKAN EVALUASI PENINGKATAN KENDALI MUTU BELAJAR ILMU SCIENCE - Mardiana (Jurnal Al Wahyu, 2023)
Character education is an important aspect of education, including vocational education. Good character education can create students with strong and moral characters. One method of implementing character education that can be done in vocational schools is through the evaluation of quality control improvement of science learning. This evaluation aims to measure the level of student understanding of science material and also to find out how far students have applied character values in their learning process. Quality control improvement evaluation of science learning can be done in various ways, one of which is by using written test methods. Written tests can be used to measure student mastery of science material theoretically. In addition, written tests can also be used to measure the level of student understanding of character values contained in science material. To be able to integrate character education into the evaluation of quality control improvement of science learning, several things need to be done. First, the science material to be tested needs to be examined first to find out the character values contained in it. Second, written test instruments need to be compiled with attention to the character values that need to be measured. Third, the process of evaluating the results of written tests needs to be carried out objectively and fairly. The evaluation of quality control improvement of science learning that integrates character education can provide great benefits for students. This evaluation can help students to improve their understanding of science material and also to develop their character.